Evaluation of Candida guilliermondii cell growth and one-pot fermentation for xylitol bioproduction - Modesto, Luiz Felipe A.; Temtemples, Manuela; Seidl, Peter Rudolf; Jr., Nei Pereira (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2016)
Xylitol is a polyalcohol with a high sweetener power that presents healthy benefits when compared to sucrose, such as prevention of caries and metabolism only partially dependent on insulin. Its bioproduction, besides being within the context of Biorefiney and Green Chemistry, presents advantages when compared to the traditional chemical process. This study analyzed Candida guilliermondii IM/UFRJ 50088 cells growth for three different operational strategies, two of them conducted on shake flasks and the other one held on instrumented bioreactor. The latter provided the best results, achieving a maximum cell productivity (Qx max) of 0.61 g/L.h while reaching cell concentrations higher than 20 g/L. For the one-pot fermentation assay, despite low xylitol yield (YP/Sâ‰ˆ0,1g/g) obtained, which shows that further research is necessary, the propagation steps were successful.